The expression and distribution of the hypoxia-inducible factors HIF-1alpha and HIF-2alpha in normal human tissues, cancers, and tumor-associated macrophages. - Talks, K; Turley, H; Gatter, K; Maxwell, P; Pugh, C; Ratcliffe, P; Harris, A (2000)
The cellular response to hypoxia includes the hypoxia-inducible factor-1 (HIF-1)-induced transcription of genes involved in diverse processes such as glycolysis and angiogenesis. Induction of the HIF-regulated genes, as a consequence of the microenvironment or genetic changes, is known to have an important role in the growth of experimental tumors. Hypoxia-inducible factors 1alpha and 2alpha (HIF-1alpha and HIF-2alpha) are known to dimerize with the aryl hydrocarbon receptor nuclear translocator in mediating this response. Because regulation of the alpha chain protein level is a primary determinant of HIF activity, our aim was to investigate the distribution of HIF-1alpha and HIF-2alpha by immunohistochemistry in normal and pathological tissues using monoclonal antibodies (mAb). We raised a new mAb to detect HIF-1alpha, designated 122, and used our previously validated mAb 190b to HIF-2alpha. In the majority of solid tumors examined, including bladder, brain, breast, colon, ovarian, pancreatic, prostate, and renal carcinomas, nuclear expression of HIF-1alpha and -2alpha was observed in varying subsets of the tumor cells. HIF-2alpha was also strongly expressed by subsets of tumor-associated macrophages, sometimes in the absence of any tumor cell expression. Less frequently staining was observed in other stromal cells within the tumors and in normal tissue adjacent to tumor margins. In contrast, in normal tissue neither molecule was detectable except within subsets of bone marrow macrophages, where HIF-2alpha was strongly expressed.